Disminución de precios de commodities en un ambiente de "enfermedad holandesa" y "bendición/maldición de los recursos naturales" - Gover Barja Daza; David Zavaleta (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2016)
– A Computable General Equilibrium model is used to analyze commodity price shocks in an abundant natural resource country framework (Bolivia), with two export oriented resource sectors (natural gas & oil and minerals) and mainly two emerging tradable sectors (food and manufacturing) with dominant import substitution orientation. The objective is to study how the structure of the Bolivian economy changed in a period of high international resource prices and anticipate how that economic structure should adjust in a new period of low international resource prices. Under what conditions will de boom reverse? Is Bolivia Prepared?
Keywords: C68; F41; F44; 330; Dutch disease; natural resource blessing/curse; CGE; external shocks; oil and gas; minerals; economic structure; boom/bust cycle